TINGKAT PENGETAHUAN DAN PERILAKU MASYARAKAT KABUPATEN WONOSOBO TENTANG COVID -19 - Ika Purnamasari; Anisa Ell Raharyani (Jurnal Ilmiah Kesehatan, 2020)
Background : Occurrences of the COVID-19 outbreak has appeared in 215 countries worldwide, one of which includes the country of Indonesia. Indonesia has been dealing with daily fluctuations of new cases of COVID-19. The death toll of patients is steadily present, yet leveled by the fact that the number of recovered is also relevant. Wonosobo is a regency with a higher increase in COVID-19 patients than its neighboring cities and regencies in the province of Central Java. The number of positive COVID-19 patients in Wonosobo currently (May 2020) stands at 64 documented cases. As an effort to reduce the increase in the number of new cases, all layers of the public and government are required to take part. Compulsory knowledge of the disease is a vital factor for the general public to act and make decisions regarding appropriateness in reducing the spread of COVID-19. Subject and Method : This research is quantitative with an analytical correlation design. The sample count is 144 respondents which were randomly chosen to fill in a Google Form which was distributed via, the application, WhatsApp to the general public of the regency of Wonosobo. The data was analysed using the Spearman Analytical Correlation method. Results : Results show that the public of Wonosobo regency who are included into the category who possess a good knowledge of COVID-19 is (90%) with only (10%) are in the category with enough knowledge. As to how the public of Wonosobo in regards with dealing with the COVID-19 pandemic, such as wearing a mask, practising hand hygiene, and physical/ social distancing shows a percentage of (95,8%) included in the good category with only (4,2%) in the enough category. There is a significant correlation between knowledge and behaviour of the public surrounding the COVID-19 pandemic with a p-value of 0,047. Conclusion : The knowledge and behaviour of the majority of the public of Wonosobo regency were categorized as good. This condition is expected to support efforts to handle the COVID-19 cases in Wonosobo to be carried out effectively. However, government and public monitoring is still required to maintain a conducive situation in an effort to stop the spread of COVID-19 Keywords : Knowledge, Behaviour, COVID-19